The Effects of a Computer-Aided Listening Comprehension Intervention on the Generalized Communication of Students With Autism Spectrum Disorder and Intellectual Disability. Issue 4 (December 2019) - Collins, Belva C.; Browder, Diane M.; Haughney, Kathryn L.; Allison, Caryn; Fallon, Kathy
In this study, a computer-aided listening comprehension intervention package supported both listening comprehension and communication goals for three students with autism spectrum disorder (ASD) and intellectual disability (ID). The package consisted of systematic instruction (i.e., system of least prompts [SLP] procedure) to teach listening comprehension, an iPad-supported electronic communication book, and a peer support arrangement. The students with ASD and ID who participated in the study increased both listening comprehension and communication skills, while showing an increase in generalizing communication turns to interactions with their peers without disabilities. The researchers found a functional relation between the SLP procedure and both dependent variables. All three participants experienced concurrent growth between the dependent variables, implying a connection between text-based listening comprehension and communication outcomes. Further implications for academic instruction for students with ASD who use augmentative and alternative communication as well as for future inquiry concerning cross-modal generalization to social communication discourse are discussed.